2019
DOI: 10.1111/jcmm.14551
|View full text |Cite
|
Sign up to set email alerts
|

Stachydrine prevents LPS‐induced bone loss by inhibiting osteoclastogenesis via NF‐κB and Akt signalling

Abstract: Osteoclast overactivation‐induced imbalance in bone remodelling leads to pathological bone destruction, which is a characteristic of many osteolytic diseases such as rheumatoid arthritis, osteoporosis, periprosthetic osteolysis and periodontitis. Natural compounds that suppress osteoclast formation and function have therapeutic potential for treating these diseases. Stachydrine (STA) is a bioactive alkaloid isolated from Leonurus heterophyllus Sweet and possesses antioxidant, anti‐inflammatory, anticancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
(81 reference statements)
3
24
0
Order By: Relevance
“…Another previous study demonstrated that stachydrine suppressed traumatic brain injury via anti-inflammatory mechanisms (Yu et al, 2018). The effects of stachydrine on immunity and inflammation have also been reported in recent studies (Cao et al, 2017;Meng et al, 2019).…”
Section: Discussionmentioning
confidence: 65%
“…Another previous study demonstrated that stachydrine suppressed traumatic brain injury via anti-inflammatory mechanisms (Yu et al, 2018). The effects of stachydrine on immunity and inflammation have also been reported in recent studies (Cao et al, 2017;Meng et al, 2019).…”
Section: Discussionmentioning
confidence: 65%
“…Among the 4 identified alkaloids, a series of inflammatory models have been applied to explore the anti-inflammatory activities and mechanisms of stachydrine and betaine. Intriguingly, stachydrine could effectively inhibit LPS-induced inflammatory bone loss by suppressing NF-κB and Akt signal pathway ( Meng et al, 2019 ), suggesting its future use in the treatment of postpartum osteoporosis. Peng and his coworkers reviewed the anti-inflammatory mechanism of betaine, that is, betaine improves sulfur amino acid metabolism against oxidative stress, suppresses NF-κB activity and NOD-like receptor protein 3 (NLRP3) inflammasome activation ( Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its activation and increased expression are key events in osteoclast differentiation. Embryonic stem cells knocked out by NFATc1 cannot differentiate into osteoclasts under the stimulation of RANKL (Meng et al, 2019). Both NF-κB and AKT signals regulate osteoclast differentiation related to NFATc1 (Ye et al, 2018;Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%